Fulfilling of the Right of Persons with Disabilities to Improve the Quality of Educational Services in The Province Of Gorontalo - Alfiyah Agussalim; Rahmatia Pakaya; Abdul Mukhlis Akuba (IHSA Institute, 2026)
As stated in the Decree of the Minister of State Apparatus Empowerment Number 63 of 2003 concerning General Guidelines for the Implementation of Public Services, the implementation of public services adheres to the principle of equal rights where there should be no discrimination in public services, including in this case for people with disabilities. To fulfill the rights of people with disabilities in educational services, the Gorontalo Provincial Government issued Governor Regulation Number 41 of 2015 concerning the Implementation of Inclusive Education in Gorontalo Province. This study aims to analyze efforts to fulfill the rights of people with disabilities, especially in the field of primary and secondary education in Gorontalo Province with a comparative approach between theory, previous research and research results. The results of this study indicate that one of the efforts made by the government is through inclusive education, but in its implementation there are still various obstacles, such as limited human resources (Special Education Teachers and Psychologists), limited employment opportunities for SLB graduates, the absence of special scholarships and lack of parental awareness to send children with special needs to school.